2019
DOI: 10.3847/1538-4357/ab22b4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive versus Free-streaming Cosmic-Ray Transport in Molecular Clouds

Abstract: Understanding the cosmic ray (CR) ionization rate is crucial in order to simulate the dynamics of, and interpret the chemical species observed in molecular clouds. Calculating the CR ionization rate requires both accurate knowledge of the spectrum of MeV to GeV protons at the edge of the cloud as well as a model for the propagation of CRs into molecular clouds. Some models for the propagation of CRs in molecular clouds assume the CRs to stream freely along magnetic field lines, while in others they propagate d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…3.1.2, the value of n H D 0 does not depend on N for a constant ionisation fraction and is determined by the velocity exponent λ of the turbu-lent spectrum. Silsbee and Ivlev (2019) showed that condition (51) is expected to hold for N 8×10 19 cm −2 for a Kolmogorov spectrum and for N 3×10 18 cm −2 for a Kraichnan spectrum. At higher column densities, the ion density is expected to drop dramatically when there are insufficient UV photons to keep carbon ionised.…”
Section: Free-streaming Versus Diffusive Penetration Of Crsmentioning
confidence: 99%
See 4 more Smart Citations
“…3.1.2, the value of n H D 0 does not depend on N for a constant ionisation fraction and is determined by the velocity exponent λ of the turbu-lent spectrum. Silsbee and Ivlev (2019) showed that condition (51) is expected to hold for N 8×10 19 cm −2 for a Kolmogorov spectrum and for N 3×10 18 cm −2 for a Kraichnan spectrum. At higher column densities, the ion density is expected to drop dramatically when there are insufficient UV photons to keep carbon ionised.…”
Section: Free-streaming Versus Diffusive Penetration Of Crsmentioning
confidence: 99%
“…it is possible to obtain simple analytical expressions for the local spectrum and corresponding ionisation rate as a function of column density. The loss function in the energy range relevant for ionisation in molecular clouds can be well approximated by (Padovani et al, 2018b;Silsbee and Ivlev, 2019)…”
Section: Free Streaming (Continuous Slowing-down Approximation)mentioning
confidence: 99%
See 3 more Smart Citations